Grammatik, Höflichkeit und Gender in der Zweiten Person.: Über Anrede-Genus - Simon, Horst (Linguistik Online, 2021)
In this paper, I study various manifestations of the grammatical category gender in address-related forms, above all in second person pronouns. It will be shown that its use is intricately connected with politeness – either because the gendered pronouns of address are themselves polite forms or because they can, under certain circumstances, convey nuances of social gender and concomitant connotations. The languages studied include, among others, Japanese, Arabic and other Semitic languages, as well as historical and dialectal varieties of German and Italian.